2014
DOI: 10.1038/srep06819
|View full text |Cite
|
Sign up to set email alerts
|

Polarity compensation in ultra-thin films of complex oxides: The case of a perovskite nickelate

Abstract: We address the fundamental issue of growth of perovskite ultra-thin films under the condition of a strong polar mismatch at the heterointerface exemplified by the growth of a correlated metal LaNiO3 on the band insulator SrTiO3 along the pseudo cubic [111] direction. While in general the metallic LaNiO3 film can effectively screen this polarity mismatch, we establish that in the ultra-thin limit, films are insulating in nature and require additional chemical and structural reconstruction to compensate for such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 52 publications
5
52
0
Order By: Relevance
“…As the reconstruction effect often appears only at the substratevacuum interface, the choice of a substrate with the same charge per plane sequence as that of the desired material can be another solution to this problem, which does not require to grow a buffer layer. To investigate this, Middey et al [64] have grown LaNiO 3 films on SrTiO 3 [with polar jump at film/substrate interface: see the upper panel of Fig. 6(a)] and LaAlO 3 [without any polar jump at film/substrate interface: see lower panel of Fig.…”
Section: Generalized Graphene Lattice From Abo 3 Perovskitesmentioning
confidence: 99%
“…As the reconstruction effect often appears only at the substratevacuum interface, the choice of a substrate with the same charge per plane sequence as that of the desired material can be another solution to this problem, which does not require to grow a buffer layer. To investigate this, Middey et al [64] have grown LaNiO 3 films on SrTiO 3 [with polar jump at film/substrate interface: see the upper panel of Fig. 6(a)] and LaAlO 3 [without any polar jump at film/substrate interface: see lower panel of Fig.…”
Section: Generalized Graphene Lattice From Abo 3 Perovskitesmentioning
confidence: 99%
“…The tendency of developing a larger gap together with higher resistivity may be due to the accumulation of disorder which is expected for polar layer growth on the (111)-oriented substrate. 20 In addition, the insulating layers in the three [2/2] SLs are very thin. With increasing stacking periodicity, electrical conduction through insulating layers may occur which leads to a higher total conductance and smaller calculated band gap.…”
Section: -mentioning
confidence: 99%
“…These polar planes have a significant effect on the growth and may lead to a surface reconstruction. 20 In 2012, Middey et al reported the synthesis of LNO/LAO heterostructures with 2/m monolayers, respectively, on mixed-terminated LAO(111) substrates. 21 Instead of the predicted Dirac-point semimetallic behavior, an activated transport was observed.…”
mentioning
confidence: 99%
“…Design of a Mott Multiferroic.-The LDA+DMFT calculations reveal that a simultaneous Mott and magnetic state could be engineered in LiOsO 3 by reducing the electronic kinetic energy. One avenue to control and decrease the kinetic energy relies on heterostructuring and interleaving two perovskites together to form a coherent superlattice, whereby an isostructural insulator would restrict the electron hopping due to the reduction in available channels [27][28][29]. Such geometries can be achieved in practice using oxide molecular-beam epitaxy or pulsed-laser deposition methods [30,31].…”
mentioning
confidence: 99%